METODE HERMENEUTIKA QUR’ANI INTEGRATIF: Analisis Linguistik-Historis atas Tafsir Surat-Surat Makkiyah M. Quraish Shihab - Piet Hizbullah Khaidir (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2025)
This study offers an in-depth analysis of the integrative Qur’anic hermeneutical methodology employed by M. Quraish Shihab in Tafsir Al-Qur’an Al-Karim: Tafsir atas Surat-Surat Pendek Berdasarkan Urutan Wahyu. The research focuses on how the integration of linguistic and historical approaches is operationalised in interpreting the short Makkah surahs that constitute the earliest sequence of revelation. The linguistic dimension encompasses semantic inquiry, Arabic structural analysis, intertextual relations, and the evolving dynamics of meaning within the milieu of early Arab society. The historical dimension involves reconstructing the social, cultural, and psychological contexts of Mecca during the period of revelation. Through this integrative hermeneutic, Shihab seeks to produce an interpretation that remains faithful to the text’s internal coherence while remaining responsive to the religious and civilisational needs of contemporary Muslim societies. Methodologically, the study combines textual analysis with a comparative hermeneutical approach to demonstrate that Shihab’s integrative method aligns with the broader currents of contemporary Qur’anic hermeneutics, while simultaneously retaining the distinctive methodological character of the Nusantara exegetical tradition. The textual analysis referred to here denotes an examination of the textual object in question, whether in the form of historical texts (for example, an analysis of the sequence of revelation and the reasons why Shihab begins his exegetical work with surat al-Fatihah) or of lexical texts (for example, the linguistic analysis employed by Shihab in examining the term al-asr). As for comparative hermeneutics, this study employs the hermeneutical theories of Hans-Georg Gadamer and Paul Ricoeur as analytical frameworks for assessing the exegetical model developed by Shihab. Accordingly, the research method adopted in this study is qualitative content analysis as the principal approach, integrated with library research and a contemporary Qur’anic hermeneutical framework. Qualitative content analysis is selected for its capacity to elucidate structures of thought, thematic patterns, and methodological relationships that are present both implicitly and explicitly in Shihab’s works. The research data consist of: (1) primary sources, namely Shihab’s work Tafsir al-Qur’an al-Karim: Tafsir atas Surat-Surat Pendek Berdasarkan Urutan Wahyu, which constitutes the main object of analysis; and (2) secondary sources, including works on hermeneutics, Qur’anic linguistics, classical and contemporary Qur’anic exegesis, as well as previous studies related to Qur’anic semantics, historical approaches, and the methodological integration of tafsir. The juxtaposition of primary and secondary data is undertaken through comparative content mapping in order to capture Shihab’s epistemological position within the landscape of modern Qur’anic hermeneutics.The findings indicate that Shihab’s integrative hermeneutic model has the potential to serve as a bridge between classical exegetical traditionalism and the demands of contextual interpretation in the modern era, particularly in matters of social ethics, religious moderation, and the articulation of the Qur’an’s universal values.